Quality of life assessment based on economic well-being perspective: A case study of Johor Bahru and Petaling, Selangor - Mohamed Osman, Mariana; Rosli, Nur Farhanah; Rabe, Noor Suzilawati (Malaysian Institute Of Planners, 2019)
The definition of quality of life is varied. Different individuals may perceive the quality of life in a different form of other individuals. Over more than four decades, Malaysia has made remarkable achievements regarding its economic growth as well as its socio-economic development. Numerous factors have been identified that may influence the quality of life of the people according to their personal preferences. This article assessed the perception of 100 respondent's lives in two major cities in Malaysia namely Johor Bharu and Petaling. These cities are also the major district in Johor Darul Takzim and Selangor Darul Ehsan. These study also would be focusing on the economic well-being of the individual. The economic individual is economic capacity, transportation, living condition and educational satisfaction.